Tris(1,10-phenathroline-k2N,N')-nickel(ii) hexaoxido-μ-peroxido-disulfate(vi) N,N-dimethylformamide disolvate monohydrate - Harvey, Miguel Angel (2013)
The asymmetric unit of the title complex, [Ni(C12H8N2)3]- S2O82C3H7NOH2O, consists of a complex [Ni(phen)3]2+ cation and one isolated pds anion, with two DMF molecules and one water molecule as solvates (where phen is 1,10- phenanthroline, pds is the hexaoxido--peroxoido-disulfate dianion and DMF is dimethylformamide). The [Ni(phen)3]2+ cation is regular, with an almost ideal NiII bond-valence sum of 2.07 v.u. The group, as well as the water solvent molecule, are well behaved in terms of crystallographic order, but the remaining three molecules in the structure display different kinds of disorder, viz. the two DMF molecules mimic a twofold splitting and the pds anion has both S atoms clamped at well-determined positions but with a not-too-well-defined central part. These peculiar behaviours are a consequence of the hydrogen-bonding interactions: the outermost SO3 parts of the pds anion are heavily connected to the complex cations via C?H O hydrogen bonding, generating an [Ni(phen)3]pds network and providing for the stability of the terminal pds sites. Also, the water solvent molecule is strongly bound to the structure (being a donor of two strong bonds and an acceptor of one) and is accordingly perfectly ordered. The peroxide O atoms in the pds middle region, instead, appear as much less restrained into their sites, which may explain their tendency to disorder. The cation?anion network leaves large embedded holes, amounting to about 28% of the total crystal volume, which are occupied by the DMF molecules. The latter are weakly interacting with the rest of the structure, which renders them much more labile and, accordingly, prone to disorder.